Orthogonal Polynomials - 18.9 Recurrence Relations and Derivatives
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
18.9#Ex1 | A_{n} = \dfrac{(2n+\alpha+\beta+1)(2n+\alpha+\beta+2)}{2(n+1)(n+\alpha+\beta+1)} |
|
A[n] = ((2*n + alpha + beta + 1)*(2*n + alpha + beta + 2))/(2*(n + 1)*(n + alpha + beta + 1)) |
Subscript[A, n] == Divide[(2*n + \[Alpha]+ \[Beta]+ 1)*(2*n + \[Alpha]+ \[Beta]+ 2),2*(n + 1)*(n + \[Alpha]+ \[Beta]+ 1)] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
18.9#Ex2 | B_{n} = \dfrac{(\alpha^{2}-\beta^{2})(2n+\alpha+\beta+1)}{2(n+1)(n+\alpha+\beta+1)(2n+\alpha+\beta)} |
|
B[n] = (((alpha)^(2)- (beta)^(2))*(2*n + alpha + beta + 1))/(2*(n + 1)*(n + alpha + beta + 1)*(2*n + alpha + beta)) |
Subscript[B, n] == Divide[(\[Alpha]^(2)- \[Beta]^(2))*(2*n + \[Alpha]+ \[Beta]+ 1),2*(n + 1)*(n + \[Alpha]+ \[Beta]+ 1)*(2*n + \[Alpha]+ \[Beta])] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
18.9#Ex3 | C_{n} = \dfrac{(n+\alpha)(n+\beta)(2n+\alpha+\beta+2)}{(n+1)(n+\alpha+\beta+1)(2n+\alpha+\beta)} |
|
C[n] = ((n + alpha)*(n + beta)*(2*n + alpha + beta + 2))/((n + 1)*(n + alpha + beta + 1)*(2*n + alpha + beta)) |
Subscript[C, n] == Divide[(n + \[Alpha])*(n + \[Beta])*(2*n + \[Alpha]+ \[Beta]+ 2),(n + 1)*(n + \[Alpha]+ \[Beta]+ 1)*(2*n + \[Alpha]+ \[Beta])] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
18.9.E3 | \JacobipolyP{\alpha}{\beta-1}{n}@{x}-\JacobipolyP{\alpha-1}{\beta}{n}@{x} = \JacobipolyP{\alpha}{\beta}{n-1}@{x} |
|
JacobiP(n, alpha, beta - 1, x)- JacobiP(n, alpha - 1, beta, x) = JacobiP(n - 1, alpha, beta, x)
|
JacobiP[n, \[Alpha], \[Beta]- 1, x]- JacobiP[n, \[Alpha]- 1, \[Beta], x] == JacobiP[n - 1, \[Alpha], \[Beta], x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E4 | (1-x)\JacobipolyP{\alpha+1}{\beta}{n}@{x}+(1+x)\JacobipolyP{\alpha}{\beta+1}{n}@{x} = 2\JacobipolyP{\alpha}{\beta}{n}@{x} |
|
(1 - x)*JacobiP(n, alpha + 1, beta, x)+(1 + x)*JacobiP(n, alpha, beta + 1, x) = 2*JacobiP(n, alpha, beta, x)
|
(1 - x)*JacobiP[n, \[Alpha]+ 1, \[Beta], x]+(1 + x)*JacobiP[n, \[Alpha], \[Beta]+ 1, x] == 2*JacobiP[n, \[Alpha], \[Beta], x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E5 | (2n+\alpha+\beta+1)\JacobipolyP{\alpha}{\beta}{n}@{x} = (n+\alpha+\beta+1)\JacobipolyP{\alpha}{\beta+1}{n}@{x}+(n+\alpha)\JacobipolyP{\alpha}{\beta+1}{n-1}@{x} |
|
(2*n + alpha + beta + 1)*JacobiP(n, alpha, beta, x) = (n + alpha + beta + 1)*JacobiP(n, alpha, beta + 1, x)+(n + alpha)*JacobiP(n - 1, alpha, beta + 1, x)
|
(2*n + \[Alpha]+ \[Beta]+ 1)*JacobiP[n, \[Alpha], \[Beta], x] == (n + \[Alpha]+ \[Beta]+ 1)*JacobiP[n, \[Alpha], \[Beta]+ 1, x]+(n + \[Alpha])*JacobiP[n - 1, \[Alpha], \[Beta]+ 1, x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E6 | (n+\tfrac{1}{2}\alpha+\tfrac{1}{2}\beta+1)(1+x)\JacobipolyP{\alpha}{\beta+1}{n}@{x} = (n+1)\JacobipolyP{\alpha}{\beta}{n+1}@{x}+(n+\beta+1)\JacobipolyP{\alpha}{\beta}{n}@{x} |
|
(n +(1)/(2)*alpha +(1)/(2)*beta + 1)*(1 + x)*JacobiP(n, alpha, beta + 1, x) = (n + 1)*JacobiP(n + 1, alpha, beta, x)+(n + beta + 1)*JacobiP(n, alpha, beta, x)
|
(n +Divide[1,2]*\[Alpha]+Divide[1,2]*\[Beta]+ 1)*(1 + x)*JacobiP[n, \[Alpha], \[Beta]+ 1, x] == (n + 1)*JacobiP[n + 1, \[Alpha], \[Beta], x]+(n + \[Beta]+ 1)*JacobiP[n, \[Alpha], \[Beta], x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E7 | (n+\lambda)\ultrasphpoly{\lambda}{n}@{x} = \lambda\left(\ultrasphpoly{\lambda+1}{n}@{x}-\ultrasphpoly{\lambda+1}{n-2}@{x}\right) |
|
(n + lambda)*GegenbauerC(n, lambda, x) = lambda*(GegenbauerC(n, lambda + 1, x)- GegenbauerC(n - 2, lambda + 1, x))
|
(n + \[Lambda])*GegenbauerC[n, \[Lambda], x] == \[Lambda]*(GegenbauerC[n, \[Lambda]+ 1, x]- GegenbauerC[n - 2, \[Lambda]+ 1, x])
|
Successful | Successful | - | Failed [6 / 90]
Result: 0.9374999999999998
Test Values: {Rule[n, 1], Rule[x, 1.5], Rule[λ, -1.5]}
Result: -0.5
Test Values: {Rule[n, 1], Rule[x, 1.5], Rule[λ, -0.5]}
... skip entries to safe data |
18.9.E8 | 4\lambda(n+\lambda+1)(1-x^{2})\ultrasphpoly{\lambda+1}{n}@{x} = -(n+1)(n+2)\ultrasphpoly{\lambda}{n+2}@{x}+(n+2\lambda)(n+2\lambda+1)\ultrasphpoly{\lambda}{n}@{x} |
|
4*lambda*(n + lambda + 1)*(1 - (x)^(2))*GegenbauerC(n, lambda + 1, x) = -(n + 1)*(n + 2)*GegenbauerC(n + 2, lambda, x)+(n + 2*lambda)*(n + 2*lambda + 1)*GegenbauerC(n, lambda, x)
|
4*\[Lambda]*(n + \[Lambda]+ 1)*(1 - (x)^(2))*GegenbauerC[n, \[Lambda]+ 1, x] == -(n + 1)*(n + 2)*GegenbauerC[n + 2, \[Lambda], x]+(n + 2*\[Lambda])*(n + 2*\[Lambda]+ 1)*GegenbauerC[n, \[Lambda], x]
|
Successful | Successful | - | Successful [Tested: 90] |
18.9.E9 | \ChebyshevpolyT{n}@{x} = \tfrac{1}{2}\left(\ChebyshevpolyU{n}@{x}-\ChebyshevpolyU{n-2}@{x}\right) |
|
ChebyshevT(n, x) = (1)/(2)*(ChebyshevU(n, x)- ChebyshevU(n - 2, x))
|
ChebyshevT[n, x] == Divide[1,2]*(ChebyshevU[n, x]- ChebyshevU[n - 2, x])
|
Successful | Failure | - | Successful [Tested: 9] |
18.9.E10 | (1-x^{2})\ChebyshevpolyU{n}@{x} = -\tfrac{1}{2}\left(\ChebyshevpolyT{n+2}@{x}-\ChebyshevpolyT{n}@{x}\right) |
|
(1 - (x)^(2))*ChebyshevU(n, x) = -(1)/(2)*(ChebyshevT(n + 2, x)- ChebyshevT(n, x))
|
(1 - (x)^(2))*ChebyshevU[n, x] == -Divide[1,2]*(ChebyshevT[n + 2, x]- ChebyshevT[n, x])
|
Successful | Failure | - | Successful [Tested: 9] |
18.9.E13 | \LaguerrepolyL[\alpha]{n}@{x} = \LaguerrepolyL[\alpha+1]{n}@{x}-\LaguerrepolyL[\alpha+1]{n-1}@{x} |
|
LaguerreL(n, alpha, x) = LaguerreL(n, alpha + 1, x)- LaguerreL(n - 1, alpha + 1, x)
|
LaguerreL[n, \[Alpha], x] == LaguerreL[n, \[Alpha]+ 1, x]- LaguerreL[n - 1, \[Alpha]+ 1, x]
|
Missing Macro Error | Successful | - | Successful [Tested: 27] |
18.9.E14 | x\LaguerrepolyL[\alpha+1]{n}@{x} = -(n+1)\LaguerrepolyL[\alpha]{n+1}@{x}+(n+\alpha+1)\LaguerrepolyL[\alpha]{n}@{x} |
|
x*LaguerreL(n, alpha + 1, x) = -(n + 1)*LaguerreL(n + 1, alpha, x)+(n + alpha + 1)*LaguerreL(n, alpha, x)
|
x*LaguerreL[n, \[Alpha]+ 1, x] == -(n + 1)*LaguerreL[n + 1, \[Alpha], x]+(n + \[Alpha]+ 1)*LaguerreL[n, \[Alpha], x]
|
Missing Macro Error | Successful | - | Successful [Tested: 27] |
18.9.E15 | \deriv{}{x}\JacobipolyP{\alpha}{\beta}{n}@{x} = \tfrac{1}{2}(n+\alpha+\beta+1)\JacobipolyP{\alpha+1}{\beta+1}{n-1}@{x} |
|
diff(JacobiP(n, alpha, beta, x), x) = (1)/(2)*(n + alpha + beta + 1)*JacobiP(n - 1, alpha + 1, beta + 1, x)
|
D[JacobiP[n, \[Alpha], \[Beta], x], x] == Divide[1,2]*(n + \[Alpha]+ \[Beta]+ 1)*JacobiP[n - 1, \[Alpha]+ 1, \[Beta]+ 1, x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E16 | \deriv{}{x}\left((1-x)^{\alpha}(1+x)^{\beta}\JacobipolyP{\alpha}{\beta}{n}@{x}\right) = -2(n+1)(1-x)^{\alpha-1}(1+x)^{\beta-1}\JacobipolyP{\alpha-1}{\beta-1}{n+1}@{x} |
|
diff((1 - x)^(alpha)*(1 + x)^(beta)* JacobiP(n, alpha, beta, x), x) = - 2*(n + 1)*(1 - x)^(alpha - 1)*(1 + x)^(beta - 1)* JacobiP(n + 1, alpha - 1, beta - 1, x)
|
D[(1 - x)^\[Alpha]*(1 + x)^\[Beta]* JacobiP[n, \[Alpha], \[Beta], x], x] == - 2*(n + 1)*(1 - x)^(\[Alpha]- 1)*(1 + x)^(\[Beta]- 1)* JacobiP[n + 1, \[Alpha]- 1, \[Beta]- 1, x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E17 | (2n+\alpha+\beta)(1-x^{2})\deriv{}{x}\JacobipolyP{\alpha}{\beta}{n}@{x} = n\left(\alpha-\beta-(2n+\alpha+\beta)x\right)\JacobipolyP{\alpha}{\beta}{n}@{x}+2(n+\alpha)(n+\beta)\JacobipolyP{\alpha}{\beta}{n-1}@{x} |
|
(2*n + alpha + beta)*(1 - (x)^(2))*diff(JacobiP(n, alpha, beta, x), x) = n*(alpha - beta -(2*n + alpha + beta)*x)*JacobiP(n, alpha, beta, x)+ 2*(n + alpha)*(n + beta)*JacobiP(n - 1, alpha, beta, x)
|
(2*n + \[Alpha]+ \[Beta])*(1 - (x)^(2))*D[JacobiP[n, \[Alpha], \[Beta], x], x] == n*(\[Alpha]- \[Beta]-(2*n + \[Alpha]+ \[Beta])*x)*JacobiP[n, \[Alpha], \[Beta], x]+ 2*(n + \[Alpha])*(n + \[Beta])*JacobiP[n - 1, \[Alpha], \[Beta], x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E18 | (2n+\alpha+\beta+2)(1-x^{2})\deriv{}{x}\JacobipolyP{\alpha}{\beta}{n}@{x} = (n+\alpha+\beta+1)\left(\alpha-\beta+(2n+\alpha+\beta+2)x\right)\JacobipolyP{\alpha}{\beta}{n}@{x}-2(n+1)(n+\alpha+\beta+1)\JacobipolyP{\alpha}{\beta}{n+1}@{x} |
|
(2*n + alpha + beta + 2)*(1 - (x)^(2))*diff(JacobiP(n, alpha, beta, x), x) = (n + alpha + beta + 1)*(alpha - beta +(2*n + alpha + beta + 2)*x)*JacobiP(n, alpha, beta, x)- 2*(n + 1)*(n + alpha + beta + 1)*JacobiP(n + 1, alpha, beta, x)
|
(2*n + \[Alpha]+ \[Beta]+ 2)*(1 - (x)^(2))*D[JacobiP[n, \[Alpha], \[Beta], x], x] == (n + \[Alpha]+ \[Beta]+ 1)*(\[Alpha]- \[Beta]+(2*n + \[Alpha]+ \[Beta]+ 2)*x)*JacobiP[n, \[Alpha], \[Beta], x]- 2*(n + 1)*(n + \[Alpha]+ \[Beta]+ 1)*JacobiP[n + 1, \[Alpha], \[Beta], x]
|
Failure | Successful | Successful [Tested: 81] | Successful [Tested: 81] |
18.9.E19 | \deriv{}{x}\ultrasphpoly{\lambda}{n}@{x} = 2\lambda\ultrasphpoly{\lambda+1}{n-1}@{x} |
|
diff(GegenbauerC(n, lambda, x), x) = 2*lambda*GegenbauerC(n - 1, lambda + 1, x)
|
D[GegenbauerC[n, \[Lambda], x], x] == 2*\[Lambda]*GegenbauerC[n - 1, \[Lambda]+ 1, x]
|
Successful | Successful | - | Successful [Tested: 90] |
18.9.E20 | \deriv{}{x}\left((1-x^{2})^{\lambda-\frac{1}{2}}\ultrasphpoly{\lambda}{n}@{x}\right) = -\frac{(n+1)(n+2\lambda-1)}{2(\lambda-1)}{(1-x^{2})^{\lambda-\frac{3}{2}}}\ultrasphpoly{\lambda-1}{n+1}@{x} |
|
diff((1 - (x)^(2))^(lambda -(1)/(2))* GegenbauerC(n, lambda, x), x) = -((n + 1)*(n + 2*lambda - 1))/(2*(lambda - 1))*(1 - (x)^(2))^(lambda -(3)/(2))*GegenbauerC(n + 1, lambda - 1, x)
|
D[(1 - (x)^(2))^(\[Lambda]-Divide[1,2])* GegenbauerC[n, \[Lambda], x], x] == -Divide[(n + 1)*(n + 2*\[Lambda]- 1),2*(\[Lambda]- 1)]*(1 - (x)^(2))^(\[Lambda]-Divide[3,2])*GegenbauerC[n + 1, \[Lambda]- 1, x]
|
Successful | Successful | - | Successful [Tested: 90] |
18.9.E21 | \deriv{}{x}\ChebyshevpolyT{n}@{x} = n\ChebyshevpolyU{n-1}@{x} |
|
diff(ChebyshevT(n, x), x) = n*ChebyshevU(n - 1, x)
|
D[ChebyshevT[n, x], x] == n*ChebyshevU[n - 1, x]
|
Successful | Successful | - | Successful [Tested: 9] |
18.9.E22 | \deriv{}{x}\left((1-x^{2})^{\frac{1}{2}}\ChebyshevpolyU{n}@{x}\right) = -(n+1){(1-x^{2})^{-\frac{1}{2}}}\ChebyshevpolyT{n+1}@{x} |
|
diff((1 - (x)^(2))^((1)/(2))* ChebyshevU(n, x), x) = -(n + 1)*(1 - (x)^(2))^(-(1)/(2))*ChebyshevT(n + 1, x)
|
D[(1 - (x)^(2))^(Divide[1,2])* ChebyshevU[n, x], x] == -(n + 1)*(1 - (x)^(2))^(-Divide[1,2])*ChebyshevT[n + 1, x]
|
Successful | Successful | - | Successful [Tested: 9] |
18.9.E23 | \deriv{}{x}\LaguerrepolyL[\alpha]{n}@{x} = -\LaguerrepolyL[\alpha+1]{n-1}@{x} |
|
diff(LaguerreL(n, alpha, x), x) = - LaguerreL(n - 1, alpha + 1, x)
|
D[LaguerreL[n, \[Alpha], x], x] == - LaguerreL[n - 1, \[Alpha]+ 1, x]
|
Missing Macro Error | Successful | - | Successful [Tested: 27] |
18.9.E24 | \deriv{}{x}\left(e^{-x}x^{\alpha}\LaguerrepolyL[\alpha]{n}@{x}\right) = (n+1)e^{-x}x^{\alpha-1}\LaguerrepolyL[\alpha-1]{n+1}@{x} |
|
diff(exp(- x)*(x)^(alpha)* LaguerreL(n, alpha, x), x) = (n + 1)*exp(- x)*(x)^(alpha - 1)* LaguerreL(n + 1, alpha - 1, x)
|
D[Exp[- x]*(x)^\[Alpha]* LaguerreL[n, \[Alpha], x], x] == (n + 1)*Exp[- x]*(x)^(\[Alpha]- 1)* LaguerreL[n + 1, \[Alpha]- 1, x]
|
Missing Macro Error | Successful | - | Successful [Tested: 27] |
18.9.E25 | \deriv{}{x}\HermitepolyH{n}@{x} = 2n\HermitepolyH{n-1}@{x} |
|
diff(HermiteH(n, x), x) = 2*n*HermiteH(n - 1, x)
|
D[HermiteH[n, x], x] == 2*n*HermiteH[n - 1, x]
|
Successful | Successful | - | Successful [Tested: 9] |
18.9.E26 | \deriv{}{x}\left(e^{-x^{2}}\HermitepolyH{n}@{x}\right) = -e^{-x^{2}}\HermitepolyH{n+1}@{x} |
|
diff(exp(- (x)^(2))*HermiteH(n, x), x) = - exp(- (x)^(2))*HermiteH(n + 1, x)
|
D[Exp[- (x)^(2)]*HermiteH[n, x], x] == - Exp[- (x)^(2)]*HermiteH[n + 1, x]
|
Successful | Successful | - | Successful [Tested: 9] |